AaABCG40 Enhances Artemisinin Content and Modulates Drought Tolerance in Artemisia annua - Fu, Xueqing; Liu, Hang; Hassani, Danial; Peng, Bowen; Yan, Xin; Wang, Yuting; Wang, Chen; Li, Ling; Liu, Pin; Pan, Qifang; Zhao, Jingya; Qian, Hongmei; et al. (Frontiers in Plant Science, 2020)
The phytohormone Abscisic acid (ABA) regulates plant growth, development, and responses to abiotic stresses, including senescence, seed germination, cold stress and drought. Several kinds of researches indicate that exogenous ABA can enhance artemisinin content in A. annua. Some transcription factors related to ABA signaling are identified to increase artemisinin accumulation through activating the artemisinin synthase genes. However, no prior study on ABA transporter has been performed in A. annua. Here, we identified a pleiotropic drug resistance (PDR) transporter gene AaPDR4/AaABCG40 from A. annua. AaABCG40 was expressed mainly in roots, leaves, buds and trichomes. GUS activity is primarily observed in roots and the vascular tissues of young leaves in proAaABCG40: GUS transgenic A. annua plants. When AaABCG40 was transferred into yeast AD12345678, yeasts expressing AaABCG40 accumulated more ABA than the control. The AaABCG40 overexpressing plants showed higher artemisinin content and stronger drought tolerance. Besides, the expression of CYP71AV1 in OE-AaABCG40 plants showed more sensitivity to exogenous ABA than that in both wild-type and iAaABCG40 plants. According to these results, they strongly suggest that AaABCG40 is involved in ABA transport in A. annua.